Guided Endodontics in Nonsurgical Retreatment of a Mandibular First Molar: A New Approach and Case Report - Maia, Lucas Moreira; Toubes, KÃªnia Maria; Moreira JÃºnior, Gil; Tonelli, Stephanie Quadros; Machado, Vinicius de Carvalho; Silveira, Frank Ferreira; Nunes, Eduardo (Iranian Endodontic Journal, 2020)
This case report describes the use of the guided endodontics for a non-surgical endodontic retreatment of the mandibular molar. A 38-year-old female reported apical swelling and localized pain on the tooth #30, exacerbated when chewing hard food. Periapical radiographic examination showed pulp canal obliteration in the apical third associated with extensive radiolucent area. Cone-beam computed tomography (CBCT) images were requested to support the diagnosis and enable preparation of a surgical guide, used to direct access to the canals that were obliterated and incompletely filled. The follow-up at 24 months radiographically showed completely healed apical area in the involved tooth. This non-surgical technique demonstrated efficacy in case resolution. Keywords: Cone-beam Computed Tomography; Endodontic; Guided Endodontics